Inspection regulation between general procedural codification and field specifics: A case study of Slovenia - Polonca Kovač (DANUBE: Law, Economics and Social Issues Review, 2016)
Inspection, as the authoritative supervision of private liable persons to comply their activities with sector-specific laws, should ensure the full implementation of public policies. Slovenia adopted the Inspection Act (IA) in 2002, in order to conduct efficient inspection, and simultaneously guarantee the defence rights of the supervised parties pursuant to the fundamental principles of the EU, the national Constitution, and general Administrative Procedure Act. This article addresses the search for a balance between general codification and sector-related specifics as stipulated by the IA, applying normative, constitutional case law and comparative methods. Special attention is dedicated to the IA rules regarding participants, their legal protection and stages of respective proceedings. It has been concluded that the most of the IA specifics are justified in order to efficiently serve the public interest. This study reveals that the Slovene IA can represent a role model for efficient yet democratic supervision in other MS as well.
Keywords: 330; Inspection; Administrative Procedure; Lex Specialis; Public Interest; Rights of Defence; EU Principles; Slovenia